2010
DOI: 10.1210/en.2009-1414
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin Regulates Prolactin Release through Hypothalamic Dopaminergic Neurons

Abstract: Prolactin (PRL) is tonically inhibited by dopamine (DA) released from neurons in the arcuate and periventricular nuclei. Kisspeptin plays a pivotal role in LH regulation. In rodents, kisspeptin neurons are found mostly in the anteroventral periventricular and arcuate nuclei, but the physiology of arcuate kisspeptin neurons is not completely understood. We investigated the role of kisspeptin in the control of hypothalamic DA and pituitary PRL secretion in adult rats. Intracerebroventricular kisspeptin-10 (Kp-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 61 publications
4
39
1
1
Order By: Relevance
“…In mice, kisspeptin regulates the prolactin release through the inhibition of hypothalamic dopaminergic neurons, whereas this mechanism depends on estradiol in female rodents [49]. These results confirm the important role played by kisspeptin in physiological regulation of HPG axis.…”
Section: Function In Puberty and Reproductive Systemsupporting
confidence: 69%
“…In mice, kisspeptin regulates the prolactin release through the inhibition of hypothalamic dopaminergic neurons, whereas this mechanism depends on estradiol in female rodents [49]. These results confirm the important role played by kisspeptin in physiological regulation of HPG axis.…”
Section: Function In Puberty and Reproductive Systemsupporting
confidence: 69%
“…Suckling stimulus suppresses the expression of tyrosine hydroxylase, a key enzyme of dopamine production, in TIDA neurons, which results in the secretion of PRL from the pituitary (Berghorn et al 2001). Recent studies have shown that kisspeptin neurons in the ARC directly project their axons to TIDA neurons (Sawai et al 2012), and that kisspeptin suppresses the activity of TIDA neurons (Szawka et al 2010). The afferent input from the SPFpc to kisspeptin neurons in the ARC observed in this study indicates a new regulatory mechanism of PRL secretion via a SPFpc-kisspeptin neuron-TIDA neuron feedback pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Monoamines and metabolites were identified based on their peak retention times. Quantification was performed using the internal standard method based on the area under the peak (Rizelio et al, 2010;Szawka et al, 2010). All samples from each brain area were measured in the same analysis.…”
Section: Neurotransmitter Analysesmentioning
confidence: 99%